Optimizing labelling conditions of 213Bi-DOTATATE for preclinical applications of peptide receptor targeted alpha therapy - Ho Sze Chan; Erik de Blois; Mark W. Konijnenberg; Alfred Morgenstern; Frank Bruchertseifer; Jeffrey P. Norenberg; Fred J. Verzijlbergen; Marion de Jong; Wouter A. P. Breeman (SpringerOpen, 2016)
Abstract Background 213Bismuth (213Bi, T1/2 = 45.6 min) is one of the most frequently used α-emitters in cancer research. High specific activity radioligands are required for peptide receptor radionuclide therapy. The use of generators containing less than 222 MBq 225Ac (actinium), due to limited availability and the high cost to produce large-scale 225Ac/213Bi generators, might complicate in vitro and in vivo applications though. Here we present optimized labelling conditions of a DOTA-peptide with an 225Ac/213Bi generator (< 222 MBq) for preclinical applications using DOTA-Tyr3-octreotate (DOTATATE), a somatostatin analogue. The following labelling conditions of DOTATATE with 213Bi were investigated; peptide mass was varied from 1.7 to 7.0 nmol, concentration of TRIS buffer from 0.15 mol.L-1 to 0.34 mol.L-1, and ascorbic acid from 0 to 71 mmol.L-1 in 800 μL. All reactions were performed at 95 °C for 5 min. After incubation, DTPA (50 nmol) was added to stop the labelling reaction. Besides optimizing the labelling conditions, incorporation yield was determined by ITLC-SG and radiochemical purity (RCP) was monitored by RP-HPLC up to 120 min after labelling. Dosimetry studies in the reaction vial were performed using Monte Carlo and in vitro clonogenic assay was performed with a rat pancreatic tumour cell line, CA20948. Results At least 3.5 nmol DOTATATE was required to obtain incorporation ≥ 99 % with 100 MBq 213Bi (at optimized pH conditions, pH 8.3 with 0.15 mol.L-1 TRIS) in a reaction volume of 800 μL. The cumulative absorbed dose in the reaction vial was 230 Gy/100 MBq in 30 min. A minimal final concentration of 0.9 mmol.L-1 ascorbic acid was required for ~100 MBq (t = 0) to minimize radiation damage of DOTATATE. The osmolarity was decreased to 0.45 Osmol/L. Under optimized labelling conditions, 213Bi-DOTATATE remained stable up to 2 h after labelling, RCP was ≥ 85 %. In vitro showed a negative correlation between ascorbic acid concentration and cell survival. Conclusion 213Bismuth-DOTA-peptide labelling conditions including peptide amount, quencher and pH were optimized to meet the requirements needed for preclinical applications in peptide receptor radionuclide therapy.